Disaster resilience and asset prices - Marco Pagano; Christian Wagner; Josef Zechner (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Using the pandemic as a laboratory, we show that asset markets assign a time- varying price to firms' disaster risk exposure. In 2020 the cross-section of realized and expected stock returns reflected firms' different exposure to the pandemic, as measured by their vulnerability to social distancing. Realized and expected return differentials initially widened and then narrowed, but disaster exposure still commanded a risk premium in December 2020. When inferred from market outcomes, resilience correlates not only with social distancing, but also with cash and environmental ratings. However, vulnerability to social distancing is the only characteristic that identifies persistently scarred firms.
Keywords: G01; G11; G12; G13; G14; Q51; Q54; 330; asset pricing; rare disasters; social distance; resilience; pandemics